Morpho-Molecular Characterization of Two Ampelomyces spp. (Pleosporales) Strains Mycoparasites of Powdery Mildew of Hevea brasiliensis - Liyanage, Kapila K.; Khan, Sehroon; Brooks, Siraprapa; Mortimer, Peter E.; Karunarathna, Samantha C.; Xu, Jianchu; Hyde, Kevin D. (Frontiers in Microbiology, 2018)
Powdery mildew disease of rubber affects immature green leaves, buds, inflorescences, and other immature tissues of rubber trees, resulting in up to 45% losses in rubber latex yield worldwide. The disease is often controlled by dusting the diseased plants with powdered sulphur, which can have long-term negative effects on the environment. Therefore, it is necessary to search for alternative and environmentally friendly control methods for this disease. This study aimed to identify mycoparasites associated with rubber powdery mildew species, and characterize them on the basis of morpho-molecular characteristics and phylogenetic analyses of ITS rDNA regions. We observed that the Ampelomyces fungus parasitizes rubber powdery mildew, and eventually destroys it. Furthermore, on the basis of phylogenetic analyses and morphological characteristics we confirmed that the Ampelomyces mycoparasite isolated from rubber powdery mildew is closely related to other mycohost taxa in the Erysiphe genus. A total of 73 (71 retrieved from GenBank and two obtained from fresh collections of rubber powdery mildew fungi) Ampelomyces sp. were analysed using ITS rDNA sequences and 153 polymorphic sites were identified through haplotypic analyses. A total of 28 haplotypes (H1-H28) were identified to have a complex network of mutation events. The results from phylogenetic tree constructed on the basis of maximum likelihood analyses, and the haplotype network tree revealed similar relationships of clustering pattern. This work presents the first report of Ampelomyces sp. as a potential biocontrol against powdery mildew disease of rubber. This work presents a potential biocontrol agent against rubber powdery mildews, which could be an alternative to synthetic chemical fungicides